español - Raposo Rivas, Manuela (2025)
The current prominence of the English language today requires teachers to implement new methodological strategies, such as game-based learning and formative assessment, as well as consider the digital context to use technological resources. This study analyzes the impact of gamification strategies on peer assessment that uses digital rubrics in a pedagogical training program for English teachers. Through a comparative and quasi-experimental case study, the analytical digital rubric is used to compare the quality and usefulness of the feedback given in the peer evaluation. One hundred and twenty-five English teachers participated, 56 in the experimental group that carried out the innovation with gamification and 69 in the control group. The results show progress in the quality of feedback they give to their peers. In conclusion, gamification strategies with the support of e-rubrics contribute to strengthening teachers' evaluative competence when giving formative feedback, while also reinforcing the practice of peer evaluation.